2023
DOI: 10.1007/s13534-023-00303-w
|View full text |Cite
|
Sign up to set email alerts
|

Towards automatic EEG cyclic alternating pattern analysis: a systematic review

Abstract: This study conducted a systematic review to determine the feasibility of automatic Cyclic Alternating Pattern (CAP) analysis. Specifically, this review followed the 2020 Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines to address the formulated research question: is automatic CAP analysis viable for clinical application? From the identified 1,280 articles, the review included 35 studies that proposed various methods for examining CAP, including the classification of A phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Different authors have proposed several solutions concerning automatic sleep analysis through CAP. Mendonça et al [17] identified three primary methods in state-of-the-art.…”
Section: State-of-the-art Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Different authors have proposed several solutions concerning automatic sleep analysis through CAP. Mendonça et al [17] identified three primary methods in state-of-the-art.…”
Section: State-of-the-art Overviewmentioning
confidence: 99%
“…Such is essential for clinical analysis, unlike the third state-of-the-art approach, which uses deep learning models [29]. The works that follow deep learning-based methodologies were reviewed by Mendonça et al [17] and are out of scope for this work.…”
Section: State-of-the-art Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the ArIs between scorers can vary not only due to uncertainties in the arousal scoring itself, but also in the sleep stage scoring (Nikkonen et al, 2024), as the latter affects the TST required in ArI computation. Approaches without relying on manually scored discrete sleep stages, for example, odds ratio product (Younes et al, 2015) and Cyclic Alternating Pattern (CAP) (Mendonça et al, 2023;Parrino et al, 2012), can provide novel insight into the assessment of sleep depth and level of arousal.…”
Section: Limitationsmentioning
confidence: 99%